Light-emitting device, preparation method of light-emitting device and electronic equipment

By incorporating gradient-arranged magnetic nanoparticle material into the hole functional layer, the problem of electron-hole transmission imbalance in the light-emitting device is solved, and the photoelectric performance and device life are improved.

CN119604126APending Publication Date: 2025-03-11GUANGDONG JUHUA RES INST OF ADVANCED DISPLAY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311164257.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-08
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Existing light-emitting devices have electron-hole transmission imbalance problems, resulting in limited improvements in photoelectric performance and device life.

Method used

A magnetic material containing the first magnetic nanoparticles to the Nth magnetic nanoparticles is incorporated into the hole functional layer, and is arranged in sequence along the direction pointing to the light emitting layer of the anode to form an energy level gradient to reduce the hole injection barrier.

Benefits of technology

The hole mobility is improved, the hole injection level of the light emitting device is improved, and the electron-hole transmission balance is promoted, thereby improving photoelectric performance and extending the device life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119604126A_ABST
    Figure CN119604126A_ABST
Patent Text Reader

Abstract

The invention discloses a light-emitting device, a preparation method of the light-emitting device and electronic equipment, and the light-emitting device comprises an anode and a cathode which are oppositely arranged, a light-emitting layer arranged between the anode and the cathode, and a hole function layer arranged between the anode and the light-emitting layer, the material of the hole function layer comprises an organic hole function material and a magnetic material comprising first to Nth magnetic nanoparticles, the average particle size of the first to Nth magnetic nanoparticles is gradually increased, and N is a positive integer greater than or equal to 2; the first magnetic nano particles to the Nth magnetic nano particles in the hole function layer are sequentially arranged in the direction from the anode to the light-emitting layer, electron-hole transmission balance of the light-emitting device is promoted, and therefore the photoelectric performance of the light-emitting device is improved, and the service life of the light-emitting device is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of optoelectronic technology, and in particular to a light-emitting device, a method for preparing a light-emitting device, and an electronic device. Background Art

[0002] A light-emitting device refers to a type of device that emits light through the injection and recombination of carriers, including but not limited to organic light-emitting diodes (OLED) and quantum dot light-emitting diodes (QLED). A light-emitting device has a "sandwich" structure, that is, it includes an anode, a cathode, and a light-emitting layer, wherein the anode and the cathode are arranged opposite to each other, and the light-emitting layer is arranged between the anode and the cathode. The light-emitting principle of a light-emitting device is: electrons are injected from the cathode of the device into the light-emitting area, holes are injected from the anode of the device into the light-emitting area, and electrons and holes recombine in the light-emitting area to form excitons, and the recombined excitons release photons in the form of radiation transition, thereby emitting light.

[0003] After years of development, light-emitting devices have made great progress in performance indicators and have shown great potential for application development. However, there are still some shortcomings, such as the device life of light-emitting devices needs to be further improved. Therefore, how to improve the device life of light-emitting devices is of great significance to the application and development of light-emitting devices. Summary of the invention

[0004] The present application provides a light-emitting device, a method for preparing the light-emitting device, and an electronic device, thereby improving the photoelectric performance and device life of the light-emitting device.

[0005] The technical solution of this application is as follows:

[0006] In a first aspect, the present application provides a light emitting device, comprising:

[0007] An anode and a cathode arranged opposite to each other;

[0008] a light-emitting layer disposed between the anode and the cathode; and

[0009] A hole functional layer is disposed between the anode and the light-emitting layer;

[0010] Among them, the material of the hole functional layer includes organic hole functional material and magnetic material, the magnetic material includes first magnetic nanoparticles to N-th magnetic nanoparticles, the average particle size of the first magnetic nanoparticles to the average particle size of the N-th magnetic nanoparticles gradually increases, and N is a positive integer greater than or equal to 2; along the direction from the anode to the light-emitting layer, the first magnetic nanoparticles to the N-th magnetic nanoparticles in the hole functional layer are arranged in sequence.

[0011] Optionally, the first magnetic nanoparticle to the Nth magnetic nanoparticle respectively carry positive charges, and / or the first magnetic nanoparticle to the Nth magnetic nanoparticle are made of the same material, and / or the first magnetic nanoparticle to the Nth magnetic nanoparticle have the same charge number; and / or

[0012] The first to Nth magnetic nanoparticles are independently selected from one or more of iron, iron alloy, iron oxide, cobalt, cobalt alloy, cobalt oxide, nickel, nickel alloy and nickel oxide.

[0013] Optionally, the particle size distribution range of the magnetic material is 1 nm to 10 nm; and / or

[0014] The N is 2, and the magnetic material consists of first magnetic nanoparticles and second magnetic nanoparticles, the average particle size of the first magnetic nanoparticles is 1nm to 6nm, and the average particle size of the second magnetic nanoparticles is 4nm to 10nm; or, the N is 3, and the magnetic material consists of first magnetic nanoparticles, second magnetic nanoparticles and third magnetic nanoparticles, the average particle size of the first magnetic nanoparticles is 1nm to 3nm, the average particle size of the second magnetic nanoparticles is 4nm to 6nm, and the average particle size of the third magnetic nanoparticles is 6nm to 10nm.

[0015] Optionally, in the hole functional layer, the mass of the first magnetic nanoparticle to the Nth magnetic nanoparticle is the same as each other; or, the mass of the first magnetic nanoparticle to the Nth magnetic nanoparticle gradually decreases; and / or

[0016] The organic hole functional material is an organic hole injection material, and the organic hole injection material is selected from poly (3,4-ethylenedioxythiophene): poly (styrene sulfonic acid), copper phthalocyanine, titanium phthalocyanine, 2,3,5,6-tetrafluoro-7,7',8,8'-tetracyanodimethyl-p-benzoquinone, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, poly (9-vinyl carbazole), poly [bis (4-phenyl) (4-butylphenyl) amine], N,N'-bis [4- [bis (3-methylphenyl) amino] phenyl] -N,N'-diphenyl-biphenyl-4,4'-diamine, 4,4',4"-tri (carbazole-9-yl) triphenylamine, poly [(9,9-dioctylfluorenyl-2,7- One or more of N,N'-diphenyl-N,N'-di(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine, N,N'-bis(1-naphthyl)-N,N'-diphenyl-1,1'-diphenyl-4,4'-diamine, 4,4'-cyclohexylbis[N,N-di(4-methylphenyl)aniline], 4,4',4'-tris(N-3-methylphenyl-N-phenylamino)triphenylamine, N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine, polythiophene, polyaniline and polytriphenylamine; and / or

[0017] The material of the hole functional layer consists of the organic hole functional material and the magnetic material.

[0018] Optionally, in the hole functional layer, the mass ratio of the magnetic material to the organic hole functional material is 1:(5-20).

[0019] In a second aspect, the present application provides a method for preparing a light-emitting device, comprising the following steps:

[0020] providing a bottom electrode, and forming a light emitting layer on one side of the bottom electrode; and

[0021] forming a top electrode on a side of the light emitting layer away from the bottom electrode;

[0022] Wherein, when the light-emitting device is of a positive structure, the bottom electrode is an anode and the top electrode is a cathode, before the step of forming a light-emitting layer on one side of the bottom electrode, the method for preparing the light-emitting device further comprises the steps of: forming a hole functional layer on one side of the bottom electrode; the light-emitting layer is formed on a side of the hole functional layer away from the bottom electrode;

[0023] Alternatively, when the light-emitting device is an inverted structure, the bottom electrode is a cathode and the top electrode is an anode, before the step of forming the top electrode on the side of the light-emitting layer away from the bottom electrode, the method for preparing the light-emitting device further comprises the steps of: forming a hole functional layer on the side of the light-emitting layer away from the bottom electrode; the top electrode is formed on the side of the hole functional layer away from the light-emitting layer;

[0024] Among them, the material of the hole functional layer includes organic hole functional material and magnetic material, the magnetic material includes first magnetic nanoparticles to N-th magnetic nanoparticles, the average particle size of the first magnetic nanoparticles to the average particle size of the N-th magnetic nanoparticles gradually increases, and N is a positive integer greater than or equal to 2; along the direction from the anode to the light-emitting layer, the first magnetic nanoparticles to the N-th magnetic nanoparticles in the hole functional layer are arranged in sequence.

[0025] Optionally, the first magnetic nanoparticle to the Nth magnetic nanoparticle respectively carry positive charges, and the method for forming the hole functional layer comprises the steps of:

[0026] (A1) depositing a dispersion containing the organic hole functional material and the magnetic material to obtain a first film layer, wherein the first magnetic nanoparticles to the Nth magnetic nanoparticles are located on a side of the first film layer close to the bottom electrode;

[0027] (A2) placing the first film layer in a first magnetic field so that the first magnetic nanoparticles to the Nth magnetic nanoparticles move in a direction away from the bottom electrode until the Nth magnetic nanoparticles to the first magnetic nanoparticles are arranged in sequence along a vertical direction away from the bottom electrode, thereby obtaining a second film layer;

[0028] (A3) Drying the second film layer to obtain the hole functional layer.

[0029] Optionally, the first magnetic field is a constant magnetic field; and / or

[0030] The magnetic field forces exerted on the first magnetic nanoparticle to the Nth magnetic nanoparticle in the first magnetic field are the same, and / or the materials of the first magnetic nanoparticle to the Nth magnetic nanoparticle are the same, and / or the charges of the first magnetic nanoparticle to the Nth magnetic nanoparticle are the same; and / or

[0031] In (A2), the magnetic field direction of the first magnetic field is parallel to a side of the first film layer away from the bottom electrode; and / or

[0032] In the step of placing the first film layer in a first magnetic field so that the first magnetic nanoparticles to the Nth magnetic nanoparticles move in a direction away from the bottom electrode, the first magnetic nanoparticles to the Nth magnetic nanoparticles respectively have velocity components in a direction perpendicular to the magnetic field direction of the first magnetic field.

[0033] Optionally, in (A1), the step of depositing a dispersion containing the organic hole functional material and the magnetic material is performed in an environment having a second magnetic field; or, after the step of depositing a dispersion containing the organic hole functional material and the magnetic material and before the step of obtaining the first film layer, the step further includes: placing the deposited dispersion in a second magnetic field; in the dispersion, the mass of the first magnetic nanoparticle to the mass of the Nth magnetic nanoparticle are the same as each other; or, the mass of the first magnetic nanoparticle to the mass of the Nth magnetic nanoparticle gradually decreases; and / or

[0034] In the dispersion, the mass ratio of the magnetic material to the organic hole functional material is 1:(5-20); and / or

[0035] The first to Nth magnetic nanoparticles are independently selected from one or more of iron, iron alloy, iron oxide, cobalt, cobalt alloy, cobalt oxide, nickel, nickel alloy and nickel oxide; and / or

[0036] The particle size distribution range of the magnetic material is 1 nm to 10 nm; and / or

[0037] The N is 2, the magnetic material consists of a first magnetic nanoparticle and a second magnetic nanoparticle, the average particle size of the first magnetic nanoparticle is 1nm to 6nm, and the average particle size of the second magnetic nanoparticle is 4nm to 10nm; or, the N is 3, the magnetic material consists of a first magnetic nanoparticle, a second magnetic nanoparticle and a third magnetic nanoparticle, the average particle size of the first magnetic nanoparticle is 1nm to 3nm, the average particle size of the second magnetic nanoparticle is 4nm to 6nm, and the average particle size of the third magnetic nanoparticle is 6nm to 10nm; and / or

[0038] The method for preparing the light-emitting device also includes the step of forming an electronic functional layer between the cathode and the light-emitting layer, wherein the material of the electronic functional layer comprises one or more of a first metal oxide, 8-hydroxyquinoline lithium, cesium carbonate, cesium fluoride, cesium azide, lithium fluoride, organic phosphorus oxide, organic thiophosphine compound and organic selenophosphine compound, wherein the first metal oxide is selected from one or more of zinc oxide, titanium oxide, tin oxide, barium oxide, tantalum oxide, aluminum oxide, zirconium oxide, magnesium zinc oxide, calcium zinc oxide, zirconium oxide, gallium zinc oxide, aluminum zinc oxide, lithium zinc oxide, titanium zinc oxide, yttrium zinc oxide, indium tin oxide and lithium titanium oxide.

[0039] Optionally, the second magnetic field is a constant magnetic field, and / or the magnetic field forces exerted on the first magnetic nanoparticle to the Nth magnetic nanoparticle in the second magnetic field are the same; and / or

[0040] The magnetic field direction of the second magnetic field is parallel to a surface of the bottom electrode close to the first film layer.

[0041] In a third aspect, the present application provides an electronic device, comprising a light-emitting device as described in any one of the first aspects, or a light-emitting device manufactured by any one of the manufacturing methods described in the second aspect.

[0042] The present application provides a light-emitting device, a method for preparing a light-emitting device, and an electronic device, which have the following technical effects:

[0043] In the light-emitting device of the present application, a magnetic material containing first to N-th magnetic nanoparticles is doped into the hole functional layer, and the first to N-th magnetic nanoparticles in the hole functional layer are arranged in sequence along the direction of the anode pointing to the light-emitting layer, so that the hole functional layer has an energy level gradient, which can reduce the barrier for hole injection into the light-emitting layer, effectively improve the hole mobility, thereby improving the hole injection level of the light-emitting device, promoting the electron-hole transfer balance of the light-emitting device, thereby improving the photoelectric performance and device life of the light-emitting device; in addition, since the first to N-th magnetic nanoparticles are orderly distributed in the hole functional layer, it can be ensured that the hole functional layer has good surface flatness.

[0044] The method for preparing the light-emitting device is suitable for large-scale industrial production. Applying the light-emitting device or the light-emitting device prepared by the method for preparing the light-emitting device to electronic devices is beneficial to improving the display effect of the electronic devices and extending the service life of the electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] The technical solution and other beneficial effects of the present application will be made apparent by describing in detail the specific implementation methods of the present application in conjunction with the accompanying drawings.

[0046] Figure 1 This is a schematic diagram of the structure of the first light-emitting device provided in the embodiments of the present application;

[0047] Figure 2 This is a schematic diagram of the structure of the first film layer in the embodiment of the present application;

[0048] Figure 3 This is a schematic diagram of the structure of the second film layer in the embodiment of the present application;

[0049] Figure 4 This is a schematic diagram of the structure of the second light-emitting device provided in the embodiments of the present application.

[0050] Reference numerals:

[0051] 1: light-emitting device, 10: substrate, 11: anode, 12: cathode, 13: light-emitting layer, 14: hole functional layer, 15: electron functional layer, 101: first film layer, 102: magnetic nanoparticles, 103: bottom electrode, 104: second film layer, 141: hole injection layer, 142: hole transport layer. DETAILED DESCRIPTION

[0052] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.

[0053] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.

[0054] It should be noted that the order of description of the following embodiments is not intended to limit the preferred order of the embodiments. In addition, in the description of the present application, the term "including" means "including but not limited to". The various embodiments of the present application may be in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single values ​​within the range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the numbered ranges, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated in this article, it is meant to include any quoted numbers (fractions or integers) within the indicated range.

[0055] In the description of the present application, the term “including” means “including but not limited to”.

[0056] The term "at least one" means one or more, and "multiple" means two or more. The term "at least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c" or "at least one of a, b and c" can be expressed as: a, b, c, ab (i.e. a and b), ac, bc or abc, where a, b and c can be single or plural, respectively.

[0057] In the present application, the description of "layer A is formed on one side of layer B" or "layer A is formed on the side of layer B away from layer C" may mean that layer A is directly formed on one side of layer B or on the side of layer B away from layer C, that is, layer A is in direct contact with layer B; it may also mean that layer A is indirectly formed on one side of layer B or on the side of layer B away from layer C, that is, other film layers may be formed between layer A and layer B.

[0058] The selection scope of the term "and / or" includes any one of two or more related listed items, and also includes any and all combinations of the related listed items, and the said any and all combinations include any combination of two related listed items, any more related listed items, or all related listed items. For example, "A and / or B" includes three parallel solutions of A, B and A+B. For another example, the technical solution of "A, and / or, B, and / or, C, and / or, D" includes any one of A, B, C, and D (that is, the technical solution connected by "logical or"), and also includes any and all combinations of A, B, C, and D, that is, the combination of any two or any three of A, B, C, and D, and also includes the combination of four items of A, B, C, and D (that is, the technical solution connected by "logical and").

[0059] The terms "gradually increase", "gradually decrease" or similar expressions should be understood in a broad sense, that is, the gradual change can be in a step-like manner or in a continuous manner.

[0060] The term "organic hole functional material" refers to a class of organic compounds that easily lose electrons to form positively charged vacancies (holes), and can achieve directional, orderly and controllable migration of holes to transport charges under the action of an electric field, and / or organic compounds that can reduce the hole injection energy barrier, including but not limited to one or more of organic hole transport materials and organic hole injection materials.

[0061] The term "magnetic material" refers to a type of material that uses the magnetic properties and magnetic effects of materials to achieve functions such as conversion, transmission, modulation, storage and detection of energy and information. Magnetic materials contain magnetic elements, including but not limited to ferromagnetic elements and one or more of rare earth elements, where examples of ferromagnetic elements are one or more of Ti, V, Cr, Mn, Fe, Co and Ni, and examples of rare earth elements are neodymium, samarium, etc.

[0062] In existing light-emitting devices, there is an unbalanced electron-hole transmission problem, which limits the improvement of the photoelectric performance and device life of the light-emitting devices. Taking QLED as an example, the low hole injection level caused by the high hole injection barrier is one of the main factors affecting the luminous efficiency and service life of QLED. Specifically, it manifests as follows: First, the hole injection of QLED is blocked, resulting in a high start-up voltage of QLED, and holes are easily accumulated at the interface of adjacent film layers, resulting in oxidation and denaturation of hole functional materials; second, the hole transmission resistance is large, causing QLED to easily heat up during operation, and the thermal effect of the film layer will accelerate the aging of each layer of functional materials, shortening the service life of QLED; third, the energy gap between the hole functional layer and the light-emitting layer is large. The level matching is not ideal, which makes it difficult to inject holes into the light-emitting layer, making the number of electrons injected into the light-emitting layer much higher than the number of holes injected into the light-emitting layer, resulting in an imbalance in electron-hole transfer, and excess electrons will make the quantum dots in the light-emitting layer negatively charged, easily forming Auger recombination, causing a sharp decline in QLED performance; fourth, excess electrons accumulate at the interface between the hole functional layer and the light-emitting layer, and the electrons will recombine with holes in the hole transport layer, causing the hole functional layer to emit light and heat, and will damage the hole functional material, thereby sharply reducing the service life and brightness of the QLED.

[0063] In order to promote the electron-hole transport balance of the light-emitting device, thereby improving the photoelectric performance and device life of the light-emitting device, the embodiment of the present application provides a light-emitting device, such as Figure 1 As shown, the light emitting device 1 includes an anode 11, a cathode 12, a light emitting layer 13 and a hole functional layer 14, wherein the anode 11 and the cathode 12 are arranged opposite to each other, the light emitting layer 13 is arranged between the anode 11 and the cathode 12, and the hole functional layer 14 is arranged between the anode 11 and the light emitting layer 13. The material of the hole functional layer 14 includes an organic hole functional material and a magnetic material, the magnetic material includes first magnetic nanoparticles to Nth magnetic nanoparticles, the average particle size of the first magnetic nanoparticles to the average particle size of the Nth magnetic nanoparticles gradually increases, and N is a positive integer greater than or equal to 2; along the direction from the anode 11 to the light emitting layer 13, the first magnetic nanoparticles to the Nth magnetic nanoparticles in the hole functional layer 14 are arranged in sequence.

[0064] In the light-emitting device 1 of the embodiment of the present application, by doping the magnetic material containing the first magnetic nanoparticles to the Nth magnetic nanoparticles into the hole functional layer 14, and in the direction of the anode pointing to the light-emitting layer, the first magnetic nanoparticles to the Nth magnetic nanoparticles in the hole functional layer are arranged in sequence, so that the hole functional layer 14 has an energy level gradient, which can reduce the barrier of hole injection into the light-emitting layer 13, effectively improve the hole mobility, thereby improving the hole injection level of the light-emitting device, promoting the electron-hole transport balance of the light-emitting device 1, and thus improving the photoelectric performance and device life of the light-emitting device 1. In addition, since the first magnetic nanoparticles to the Nth magnetic nanoparticles are orderly distributed in the hole functional layer 14, it can be ensured that the hole functional layer 14 has good surface flatness.

[0065] In order to further improve the hole injection level of the light-emitting device 1, in some embodiments of the present application, the first magnetic nanoparticle to the Nth magnetic nanoparticle respectively carry positive charges, which can increase the number of holes injected into the light-emitting layer 13. Further, in order to facilitate the control of the quality of the hole functional layer 14, in some embodiments of the present application, the first magnetic nanoparticle to the Nth magnetic nanoparticle are made of the same material, and / or the first magnetic nanoparticle to the Nth magnetic nanoparticle have the same charge number.

[0066] In some embodiments of the present application, the first magnetic nanoparticle to the Nth magnetic nanoparticle are independently selected from one or more of iron, iron alloy, iron oxide, cobalt, cobalt alloy, cobalt oxide, nickel, nickel alloy and nickel oxide. Among them, the iron alloy includes but is not limited to one or more of FeCr alloy, FeNi alloy, FeCrMo alloy, FeCo alloy and FeCrCo alloy; the iron oxide includes but is not limited to Fe3O4 or Fe2O3 with magnetic groups modified on the surface; the cobalt alloy includes but is not limited to one or more of SmCo alloy, CoCrMo alloy and CoCr alloy; the cobalt oxide includes but is not limited to one or more of Co3O4 and Co2O3; the nickel alloy includes but is not limited to one or more of AlNiCo alloy, FeNiSi alloy and NiV alloy; the nickel oxide includes but is not limited to NiO. As an example, the materials of the first magnetic nanoparticle to the Nth magnetic nanoparticle are all Fe3O4.

[0067] It should be noted that magnetic nanoparticles carrying positive or negative charges have been commercially produced and can be purchased commercially or prepared using conventional methods in the art.

[0068] In order to further improve the hole injection level of the light-emitting device 1 and the surface flatness of the hole functional layer 14, in some embodiments of the present application, the mass of the first magnetic nanoparticle to the Nth magnetic nanoparticle is the same as each other; or, the mass of the first magnetic nanoparticle to the Nth magnetic nanoparticle gradually decreases.

[0069] In order to further improve the hole injection level of the light-emitting device 1 and the surface flatness of the hole functional layer 14 , in some embodiments of the present application, the particle size distribution range of the magnetic material is 1 nm to 10 nm.

[0070] In some embodiments of the present application, N is 2, and the magnetic material is composed of a first magnetic nanoparticle and a second magnetic nanoparticle. The average particle size of the first magnetic nanoparticle is 1nm to 6nm, for example, the average particle size of the first magnetic nanoparticle is 1nm, 2nm, 3nm, 4nm, 5nm, 6nm or a value between any two of the aforementioned values. The average particle size of the second magnetic nanoparticle is 4nm to 10nm, for example, the average particle size of the second magnetic nanoparticle is 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm or a value between any two of the aforementioned values. It is understandable that there is a partial overlap between the average particle size range of the first magnetic nanoparticles and the average particle size range of the second magnetic nanoparticles, but the actual selection needs to meet the premise that the average particle size of the second magnetic nanoparticles is greater than the average particle size of the first magnetic nanoparticles.

[0071] In other embodiments of the present application, the magnetic material is composed of first magnetic nanoparticles, second magnetic nanoparticles and third magnetic nanoparticles. The average particle size of the first magnetic nanoparticles is 1nm to 3nm, for example, 1nm, 2nm, 3nm or a value between any two of the aforementioned values. The average particle size of the second magnetic nanoparticles is 4nm to 6nm, for example, 4nm, 5nm, 6nm or a value between any two of the aforementioned values, and the average particle size of the third magnetic nanoparticles is 6nm to 10nm, for example, 6nm, 7nm, 8nm, 9nm, 10nm or a value between any two of the aforementioned values. It can be understood that the actual selection needs to meet the premise that the average particle size of the first magnetic nanoparticles to the average particle size of the third magnetic nanoparticles gradually increases.

[0072] The hole function layer 14 may be a single-layer structure or a multi-layer structure. The thickness of the hole function layer 14 is, for example, 10 nm to 100 nm.

[0073] When the hole functional layer 14 is a single-layer structure, in some embodiments of the present application, the material of the hole functional layer is composed of the organic hole functional material and the magnetic material. The organic hole functional material can be, for example, an organic hole injection material or an organic hole transport material. The organic hole injection material or the organic hole transport material can be selected from conventional materials in the art. The organic hole injection material includes, but is not limited to, poly(3,4-ethylenedioxythiophene): poly(styrenesulfonic acid), copper phthalocyanine, titanium phthalocyanine, 2,3,5,6-tetrafluoro-7,7',8,8'-tetracyanodimethyl-p-benzoquinone, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, poly(9-vinylcarbazole), poly[bis(4-phenyl)(4-butylphenyl)amine], N,N'-bis[4-[bis(3-methylphenyl)amino]phenyl]-N,N'-diphenyl-biphenyl-4,4'-diamine, 4 ,4',4"-tri(carbazole-9-yl)triphenylamine, poly[(9,9-dioctylfluorenyl-2,7-diyl)-co-(4,4'-(N-(p-butylphenyl))diphenylamine)], 4,4'-bis(N-carbazole)-1,1'-biphenyl, N,N'-diphenyl-N,N'-di(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine, N,N'-bis(1-naphthyl)-N,N'-diphenyl-1,1'-diphenyl-4,4'-diamine, 4,4'-cyclohexylbis[N,N-di(4-methylphenyl)aniline], 4,4',4'-tri(N-3-methylphenyl-N-phenylamino)triphenylamine, N ,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine, polythiophene, polyaniline and polytriphenylamine, the organic hole transport material includes but is not limited to 3-hexyl substituted polythiophene, poly(9-vinylcarbazole), 4,4'-di(9-carbazole)biphenyl, poly[bis(4-phenyl)(4-butylphenyl)amine], 4,4'-cyclohexylbis[N,N-di(4-methylphenyl)aniline], poly[(9,9-dioctylfluorenyl-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine)], poly[(9,9-dioctylfluorenyl-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine)] -(4,4'-(N-(p-butylphenyl))diphenylamine)], poly(N,N'-di(4-butylphenyl)-N,N'-diphenyl-1,4-phenylenediamine-co-9,9-dioctylfluorene), 4,4',4'-tri(N-3-methylphenyl-N-phenylamino)triphenylamine, 4,4',4"-tri(carbazol-9-yl)triphenylamine, 4,4',4'-tri(2-naphthylphenylamino)triphenylamine, N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine, N,N'-diphenyl-N,N'-di(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine, N,One or more of N'-bis[4-(diphenylamino)phenyl]-N,N'-diphenylbenzidine, N,N'-bis(3-methylphenyl)-N,N'-diphenyl-9,9-spirobifluorene-2,7-diamine, N2,N7-di-1-naphthyl-N2,N7-diphenyl-9,9'-spirobi[9H-fluorene]-2,7-diamine, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] and 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene.

[0074] When the hole functional layer 14 is a multi-layer structure, the hole functional layer 14 includes but is not limited to one or more of a hole injection layer, a hole transport layer and an electron blocking layer. For the hole functional layer 14 including the hole injection layer, the hole transport layer and the electron blocking layer, the hole injection layer, the hole transport layer and the electron blocking layer can be arranged in sequence, and the hole injection layer is closer to the anode 11 than the electron blocking layer. In some embodiments of the present application, the material of the hole injection layer is composed of the organic hole functional material and the magnetic material, and the corresponding organic hole functional material is an organic hole injection material. The material of the hole transport layer or the electron blocking layer can select conventional materials in the field. For example, in addition to being selected from any one or more of the aforementioned organic hole transport materials, the material of the hole transport layer can also be selected from inorganic hole transport materials. The inorganic hole transport materials include but are not limited to one or more of doped or undoped graphene, C60, doped or undoped nickel oxide, doped or undoped molybdenum oxide, doped or undoped tungsten oxide, doped or undoped vanadium oxide, doped or undoped P-type gallium nitride, doped or undoped chromium oxide, doped or undoped copper oxide, transition metal sulfides and transition metal selenides. Among them, transition metal sulfides include but are not limited to one or more of molybdenum sulfide, tungsten sulfide and copper sulfide; transition metal selenides include but are not limited to one or more of molybdenum selenide and tungsten selenide; doped or undoped nickel oxide is exemplified by NiO, doped or undoped molybdenum oxide is exemplified by MoO3, doped or undoped tungsten oxide is exemplified by WO3, doped or undoped vanadium oxide is exemplified by V2O5, doped or undoped chromium oxide is exemplified by CrO3, and doped or undoped copper oxide is exemplified by one or more of CuO and Cu2O.

[0075] In order to further improve the hole injection level of the light-emitting device 1 and the surface flatness of the hole functional layer 14, in some embodiments of the present application, the mass ratio of the magnetic material to the organic hole functional material is 1:(5-20), for example, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19, 1:20 or a value between any two of the foregoing ratios.

[0076] In some embodiments of the present application, the materials of the anode 11 and the cathode 12 are independently selected from one or more of metals, carbon materials and second metal oxides, wherein the metals include but are not limited to one or more of Al, Ag, Cu, Mo, Au, Ba, Pt, Ca, Ir, Ni and Mg, the carbon materials include but are not limited to one or more of graphite, carbon nanotubes, graphene and carbon fibers, and the third metal oxides include but are not limited to one or more of indium tin oxide (ITO), fluorine-doped tin oxide (FTO), antimony tin oxide (ATO), aluminum-doped zinc oxide (AZO), gallium-doped zinc oxide (GZO), indium-doped zinc oxide (IZO), magnesium-doped zinc oxide (MZO), SnO2, ZnO and In2O3. The anode 11 or the cathode 12 may also be a composite electrode, which has a structure similar to a "sandwich", wherein the materials of the upper and lower layers are respectively doped or undoped transparent metal oxides, and the material of the middle layer is a metal, for example, it may be one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2, and the thickness of the middle layer does not exceed 35nm. The thickness of the anode 11 may be, for example, 20nm to 300nm, and the thickness of the cathode 12 may be, for example, 20nm to 300nm.

[0077] The light emitting layer 13 is a single layer structure or a multilayer structure. The light emitting layer 13 may be two or more layers. The thickness of the light emitting layer 13 may be 10 nm to 100 nm. In some embodiments of the present application, the material of the light emitting layer 13 includes one or more organic light emitting materials and quantum dots.

[0078] Among them, the organic light-emitting materials include but are not limited to 4,4'-bis(N-carbazole)-1,1'-biphenyl:tri[2-(p-tolyl)pyridine iridium(III), 4,4',4"-tri(carbazole-9-yl)triphenylamine:tri[2-(p-tolyl)pyridine iridium, diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials, DBP fluorescent materials, delayed fluorescent materials, TTA materials, thermally activated delayed materials, polymers containing BN covalent bonds, hybrid localized charge transfer excited state materials and exciplex light-emitting materials. One or more.

[0079] Quantum dots include but are not limited to one or more of red quantum dots, green quantum dots and blue quantum dots, and quantum dots include but are not limited to one or more of single component quantum dots, core-shell structure quantum dots, inorganic perovskite quantum dots, organic perovskite quantum dots and organic-inorganic hybrid perovskite quantum dots. The average particle size of the quantum dots can be, for example, 2nm to 20nm, and the average particle size of the quantum dots is exemplified as 2nm, 5nm, 8nm, 10nm, 15nm, 18nm, 20nm or a value between any two of the foregoing values.

[0080] For single-component quantum dots and core-shell structure quantum dots, the material of the single-component quantum dots, the material of the core of the core-shell structure quantum dots or the material of the shell of the core-shell structure quantum dots is, but is not limited to, at least one of a II-VI group compound, a III-V group compound, a IV-VI group compound or a I-III-VI group compound, wherein the II-VI group compound is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, Zn One or more of CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and the III-V compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, Al As, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, I nPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNA s, InAlNSb, InAlPAs and InAlPSb, the IV-VI group compound is selected from one or more of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe and SnPbSTe, and the I-III-VI group compound is selected from one or more of CuInS, CuInSe and AgInS. It should be noted that for the material of the aforementioned single-component quantum dots, or the material of the core of the core-shell structure quantum dots, or the material of the shell of the core-shell structure quantum dots, the chemical formula provided only indicates the elemental composition, and does not indicate the content of each element. For example: CdZnSe only indicates that it is composed of three elements: Cd, Zn and Se. If the content of each element is indicated, it corresponds to Cd x Zn 1-x Se,0 <x<1。

[0081] For inorganic perovskite quantum dots, the general structural formula of inorganic perovskite quantum dots is AMX3, where A is Cs + ion, M is a divalent metal cation, M includes but is not limited to Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ or Eu 2+ , X is a halogen anion, including but not limited to Cl - Br - or I - .

[0082] For organic perovskite quantum dots, the general structural formula of organic perovskite quantum dots is CMX3, wherein C is a carboxamidine group, and M is a divalent metal cation, and M includes but is not limited to Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ or Eu 2+ , X is a halogen anion, including but not limited to Cl - Br - or I - .

[0083] For organic-inorganic hybrid perovskite quantum dots, the general structural formula of organic-inorganic hybrid perovskite quantum dots is BMX3, wherein B is selected from organic amine cations, and the organic amine cations include but are not limited to CH3(CH2) n-2 NH 3+ (n≥2) or NH3(CH2) n NH3 2+ (n≥2), M is a divalent metal cation, including but not limited to Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe2+ ,Ge 2+ , Yb 2+ or Eu 2+ , X is a halogen anion, including but not limited to Cl - Br - or I - .

[0084] It is understood that when the material of the light-emitting layer 13 includes quantum dots, the material of the light-emitting layer 13 also includes ligands connected to the surface of the quantum dots, and the ligands include but are not limited to hydroxyl, amino, thiol, carboxyl, C1-C 30 Fatty carboxylic acid ligands, C6~C 30 Aromatic carboxylic acid ligands, C1~C 30 Aliphatic thiol ligands, C6~C 30 Thiol aromatic ligands, C1~C 30 Fatty amine ligands, C6~C 30 Aromatic amine ligands, C1~C 30 Aliphatic phosphine ligands, C1~C 30 Aromatic phosphine ligands and C1~C 30 One or more of aromatic phosphate ligands and halogen ligands.

[0085] Among them, the fatty carboxylic acid ligands include but are not limited to one or more of octanoic acid, nonanoic acid, decanoic acid, undecanoic acid, dodecanoic acid, tetradecanoic acid, hexadecanoic acid, octadecanoic acid, eicosanoic acid, tetracosanoic acid, hexacosanoic acid, oleic acid, linoleic acid, arachidic acid, arachidonic acid, erucic acid and docosahexaenoic acid; the aromatic carboxylic acid ligands include but are not limited to one or more of benzoic acid, dibenzoic acid and 1-naphthoic acid. The fatty thiol ligands include, but are not limited to, one or more of hexyl mercaptan, octyl mercaptan, nonyl mercaptan, decanyl mercaptan, undecanyl mercaptan, dodecanyl mercaptan, hexadecanyl mercaptan and octadecyl mercaptan. The thiol aromatic ligands include, but are not limited to, one or more of benzene mercaptan, triphenylmethyl mercaptan and p-terphenyl-4,4"-dithiol. The fatty amine ligands include, but are not limited to, one or more of hexylamine, octylamine, dioctylamine, trioctylamine, nonylamine, decylamine, dodecylamine, tridecylamine, tetradecylamine, pentadecylamine, hexadecylamine, heptadecanylamine, octadecylamine and oleylamine. The aromatic amine ligands include, but are not limited to, aniline, indenepropylamine, 4-octylaniline and and one or more of benzidine. Aliphatic phosphine ligands include but are not limited to one or more of trimethylphosphine, triethylphosphine, tripropylphosphine, tributylphosphine, trihexylphosphine, trioctylphosphine, tridecylphosphine, tributylphosphine oxide, trihexylphosphine oxide, trioctylphosphine oxide and tridecylphosphine oxide, aromatic phosphine ligands include but are not limited to one or more of bis(2-diphenylphosphinoethyl)phenylphosphine and triphenylphosphine oxide, aromatic phosphate ligands include but are not limited to one or more of tetraethyl p-xylene diphosphate and diphenylethyl phosphate. Halogen ligands include but are not limited to -Cl, -F, -I or -Br.

[0086] In order to further improve the comprehensive performance of the light emitting device 1, in some embodiments of the present application, continue to refer to Figure 1 The light-emitting device further includes an electronic functional layer 15, which is disposed between the cathode 12 and the light-emitting layer 13; the thickness of the electronic functional layer 15 is, for example, 10 nm to 100 nm. The electronic functional layer 15 can be a single-layer structure or a multi-layer structure, and the electronic functional layer 15 can include, for example, one or more of an electron injection layer, an electron transport layer, and a hole blocking layer. For the electronic functional layer 15 including the electron injection layer, the electron transport layer, and the hole blocking layer, the electron injection layer, the electron transport layer, and the hole blocking layer can be disposed in sequence, and the electron injection layer is closer to the cathode 12 than the hole blocking layer.

[0087] The material of the electronic functional layer 15 includes, but is not limited to, one or more of a first metal oxide, a II-VI semiconductor material, a III-V semiconductor material, a I-III-VI semiconductor material, 8-hydroxyquinoline lithium, cesium carbonate, cesium fluoride, cesium azide, lithium fluoride, organic phosphorus oxide, organic thiophosphine compound, and organic selenium phosphine compound. The first metal oxide may be doped or undoped, and the undoped first metal oxide may be selected from one or more of ZnO, TiO2, SnO2, BaO, Ta2O3, Al2O3, and ZrO2, and the doped first metal oxide may be selected from one or more of zinc oxide magnesium, zinc oxide calcium, zinc oxide zirconium, zinc oxide gallium, zinc oxide aluminum, zinc oxide lithium, zinc oxide titanium, yttrium zinc oxide, indium tin oxide, and titanium oxide lithium, exemplified by ZnO. (1-x) Mg x O, Zn (1-x) Ca x O, Zn (1-x) Zr x O, Zn (1-x) Ga x O, Zn (1-x) Al x O, Zn (1-x) Li x O、Al (1-x) Zn x O, Zn (1-x) Ti x O, Zn (1-x) Y x O、In (1-x) Sn x O and Ti (1-x) Li x O, wherein 0<x≤0.5. The II-VI semiconductor material is selected from one or more of ZnS, ZnSe and CdS. The III-V semiconductor material is selected from one or more of InP and GaP. The I-III-VI semiconductor material is selected from one or more of CuInS and CuGaS.

[0088] The embodiment of the present application also provides a method for preparing a light-emitting device, which can be used to prepare any of the light-emitting devices described above, comprising the following steps:

[0089] S1. providing a bottom electrode and forming a light-emitting layer on one side of the bottom electrode;

[0090] S2. Form a top electrode on a side of the light-emitting layer away from the bottom electrode.

[0091] Wherein, when the light-emitting device is a positive structure, the bottom electrode is an anode and the top electrode is a cathode, and before the step of forming a light-emitting layer on one side of the bottom electrode in S1, the method for preparing the light-emitting device further comprises the steps of: forming a hole functional layer on one side of the bottom electrode; and forming the light-emitting layer on the side of the hole functional layer away from the bottom electrode. Alternatively, when the light-emitting device is an inverted structure, the bottom electrode is a cathode and the top electrode is an anode, and between S1 and S2, the method for preparing the light-emitting device comprises the steps of: forming a hole functional layer on the side of the light-emitting layer away from the bottom electrode, and forming the top electrode on the side of the hole functional layer away from the light-emitting layer. Wherein, the material of the hole functional layer comprises an organic hole functional material and a magnetic material, and the magnetic material comprises a first magnetic nanoparticle to an Nth magnetic nanoparticle, and the average particle size of the first magnetic nanoparticle to the average particle size of the Nth magnetic nanoparticle gradually increases, and N is a positive integer greater than or equal to 2; along the direction from the anode to the light-emitting layer, the first magnetic nanoparticle to the Nth magnetic nanoparticle are arranged in sequence. The specific conditions of the hole functional layer, the organic hole functional material, the magnetic material, the anode, the cathode and the light-emitting layer can refer to the above description.

[0092] In order to further improve the hole injection level of the light-emitting device and the surface flatness of the hole functional layer, and simplify the preparation process, in some embodiments of the present application, the first magnetic nanoparticle to the Nth magnetic nanoparticle respectively carry positive charges, and the method for forming the hole functional layer includes the steps of:

[0093] (A1) depositing a dispersion containing an organic hole functional material and a magnetic material to obtain a first film layer, wherein the first magnetic nanoparticles to the Nth magnetic nanoparticles are located on a side of the first film layer close to the bottom electrode;

[0094] (A2) placing the first film layer in a first magnetic field so that the first magnetic nanoparticles to the Nth magnetic nanoparticles move in a direction away from the bottom electrode until the Nth magnetic nanoparticles to the first magnetic nanoparticles are arranged in sequence along a vertical direction away from the bottom electrode, thereby obtaining a second film layer;

[0095] (A3) Drying the second film layer to obtain a hole functional layer.

[0096] In the above-mentioned method for forming the hole functional layer, the first film layer is treated with a first magnetic field so that the first magnetic nanoparticles to the Nth magnetic nanoparticles are distributed in a gradient in the second film layer, providing an efficient transmission channel for holes, thereby greatly improving the hole injection efficiency and ensuring that the hole functional layer has good surface flatness.

[0097] Figure 2The schematic diagram of the structure of the first film layer is shown, wherein the first film layer is 101, the magnetic nanoparticles are 102, and the bottom electrode is 103. In (A1), the dispersant of the dispersion is an organic compound in which both the organic hole functional material and the magnetic material have good dispersibility, including but not limited to one or more of alkane compounds, aromatic hydrocarbon compounds and alcohol compounds, wherein the alkane compounds include unsubstituted alkanes and / or halogenated alkanes, the aromatic hydrocarbon compounds include unsubstituted aromatic hydrocarbons and / or halogenated aromatic hydrocarbons, and the alcohol compounds include unsubstituted alcohols and / or halogenated alcohols. The alkane compound can be, for example, an alkane with a carbon number of 1 to 20, an alkane with a carbon number of 1 to 10, or an alkane with a carbon number of 1 to 6, exemplified by one or more of n-octane, n-hexane, n-heptane, n-nonane, dichloromethane, chloroform and carbon tetrachloride. Aromatic hydrocarbon compounds may be aromatic hydrocarbons having 6 to 20 carbon atoms, aromatic hydrocarbons having 12 to 20 carbon atoms, aromatic hydrocarbons having 6 to 12 carbon atoms, or aromatic hydrocarbons having 8 to 18 carbon atoms, and examples thereof include one or more of toluene, diethylbenzene, trimethylbenzene, propylbenzene, isopropylbenzene, p-toluene isopropylbenzene, cyclohexylbenzene, butylbenzene, 1-methylnaphthalene, chlorobenzene, and indene. Alcohol compounds may be, for example, alcohols having 1 to 20 carbon atoms, alcohols having 1 to 10 carbon atoms, or alcohols having 1 to 6 carbon atoms, and examples thereof include one or more of methanol, ethanol, propanol, butanol, ethylene glycol, and glycerol.

[0098] In order to improve the processability of the dispersion, in some embodiments of the present application, the total concentration of the magnetic material in the dispersion is 0.5 mg / mL to 1 mg / mL, for example, it can be 0.5 mg / mL, 0.6 mg / mL, 0.7 mg / mL, 0.8 mg / mL, 0.9 mg / mL, 1 mg / mL or a value between any two of the foregoing values.

[0099] In order to further improve the hole injection level of the light-emitting device and the surface flatness of the hole functional layer, in some embodiments of the present application, the mass ratio of the magnetic material to the organic hole functional material in the dispersion is 1:(5-20), for example, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19, 1:20 or a value between any two of the foregoing ratios.

[0100] In order to further improve the hole injection level of the light-emitting device and the surface flatness of the hole functional layer, in some embodiments of the present application, in the dispersion (A1), the mass of the first magnetic nanoparticles to the Nth magnetic nanoparticles are the same as each other; or, the mass of the first magnetic nanoparticles to the Nth magnetic nanoparticles gradually decreases.

[0101] In some embodiments of the present application, the deposition method of the dispersion includes but is not limited to one or more of spin coating, printing, inkjet printing, doctor blading, printing, dip pulling, immersion, spraying, roll coating, casting, slit coating, strip coating and solution electrodeposition.

[0102] In order to make the magnetic material deposit quickly on the side of the first film layer close to the bottom electrode, in some embodiments of the present application, in (A1), the step of depositing the dispersion containing the organic hole functional material and the magnetic material is carried out in the environment of a second magnetic field; or, after the step of depositing the dispersion containing the organic hole functional material and the magnetic material and before the step of obtaining the first film layer, it also includes the step of applying a second magnetic field to the deposited dispersion.

[0103] In order to facilitate the control of the preparation process, in some embodiments of the present application, the second magnetic field is a constant magnetic field, and / or the magnetic field forces received by the first magnetic nanoparticle to the Nth magnetic nanoparticle in the second magnetic field are the same. In order to facilitate the control of the magnetic field forces received by the first magnetic nanoparticle to the Nth magnetic nanoparticle in the second magnetic field to be the same, the charge numbers of the first magnetic nanoparticle to the Nth magnetic nanoparticle can be made the same. It can be understood that the second magnetic field can be a uniform magnetic field or a non-uniform magnetic field. When the second magnetic field is a non-uniform magnetic field, the second magnetic field can be made uniform in the region where the first magnetic nanoparticle to the Nth magnetic nanoparticle are located to ensure that the magnetic field forces received by the first magnetic nanoparticle to the Nth magnetic nanoparticle in the second magnetic field are the same.

[0104] Further, the magnetic field direction of the second magnetic field is parallel to the side of the bottom electrode close to the first film layer. Further, when the first magnetic nanoparticle to the Nth magnetic nanoparticle moves in the direction close to the bottom electrode, the first magnetic nanoparticle to the Nth magnetic nanoparticle respectively have a velocity component in the direction perpendicular to the magnetic field direction of the first magnetic field. By controlling the deposition thickness of the first film layer, the movement radius of the magnetic nanoparticles and the processing time of the second magnetic field (which can be achieved by those skilled in the art based on common knowledge), the first magnetic nanoparticle to the Nth magnetic nanoparticle can be made to move approximately in a straight line in a short time, thereby being deposited on the side of the first film layer close to the bottom electrode. As an example, the deposition thickness of the first film layer is 10nm to 100nm, and / or the processing time of the second magnetic field is 5s to 30s.

[0105] In step (A2), Figure 3The schematic diagram of the structure of the second film layer is shown, wherein the second film layer is 104, the magnetic nanoparticles are 102, and the bottom electrode is 103. In order to facilitate the control of the preparation process, in some embodiments of the present application, the first magnetic field is a constant magnetic field, and / or the magnetic field force received by the first magnetic nanoparticle to the Nth magnetic nanoparticle in the first magnetic field is the same, and / or the materials of the first magnetic nanoparticle to the Nth magnetic nanoparticle are the same, and / or the charge numbers of the first magnetic nanoparticle to the Nth magnetic nanoparticle are the same. When the magnetic field force received by the first magnetic nanoparticle to the Nth magnetic nanoparticle in the first magnetic field is the same, under the action of the first magnetic field, the smaller the mass of the magnetic nanoparticle (for magnetic nanoparticles of the same material, the smaller the average particle size, the smaller the mass) the greater the motion acceleration, so that the first magnetic nanoparticle to the Nth magnetic nanoparticle presents a gradient distribution in the second film layer. As mentioned above, the first magnetic field can be a uniform magnetic field or a non-uniform magnetic field. When the first magnetic field is a non-uniform magnetic field, the first magnetic field can be uniform in the region where the first magnetic nanoparticles to the Nth magnetic nanoparticles are located, so as to ensure that the magnetic field forces exerted on the first magnetic nanoparticles to the Nth magnetic nanoparticles in the first magnetic field are the same.

[0106] Further, the magnetic field direction of the first magnetic field is parallel to the side of the bottom electrode close to the first film layer. Further, in the step of placing the first film layer in the first magnetic field so that the first magnetic nanoparticles to the Nth magnetic nanoparticles move in the direction away from the bottom electrode, the first magnetic nanoparticles to the Nth magnetic nanoparticles respectively have velocity components in the direction perpendicular to the magnetic field direction of the first magnetic field. By controlling the deposition thickness of the first film layer, the movement radius of the magnetic nanoparticles and the treatment time of the first magnetic field (which can be achieved by those skilled in the art based on common knowledge), the first magnetic nanoparticles to the Nth magnetic nanoparticles can be made to move approximately linearly in a short time, so that the first magnetic nanoparticles to the Nth magnetic nanoparticles finally present a gradient distribution. As an example, the deposition thickness of the first film layer is 10nm to 100nm, and / or the treatment time of the first magnetic field is 5s to 15s.

[0107] When the magnetic field direction of the first magnetic field is parallel to the side of the bottom electrode close to the first film layer, and the magnetic field direction of the second magnetic field is parallel to the side of the bottom electrode close to the first film layer, the magnetic field direction of the first magnetic field is opposite to the magnetic field direction of the second magnetic field, that is, the N pole of the first magnetic field corresponds to the S pole of the second magnetic field, and the S pole of the first magnetic field corresponds to the N pole of the second magnetic field.

[0108] In (A3), "drying treatment" includes all processes that can make the second film layer obtain higher energy and transform into a solidified film layer, including but not limited to heating treatment or vacuum drying treatment, wherein the temperature of the heating treatment can be constant temperature or non-constant temperature (for example, the temperature changes in a gradient). As an example, the drying treatment is a heating treatment, and the temperature of the heating treatment is 60°C to 300°C.

[0109] In some other embodiments of the present application, the method for forming the hole functional layer includes the steps of: sequentially forming the first hole functional sublayer to the Nth hole functional sublayer, the first hole functional sublayer to the Nth hole functional sublayer respectively contain a type of magnetic nanoparticle, that is, the first hole functional sublayer contains the first magnetic nanoparticle, and by analogy, the Nth hole functional sublayer contains N magnetic nanoparticles, and the first hole functional sublayer to the Nth hole functional sublayer also respectively contain organic hole functional materials. Each hole functional sublayer can be prepared by a solution method, for example, depositing a solution containing magnetic nanoparticles and an organic hole functional material, and then drying the deposited solution to solidify it into a film.

[0110] In some embodiments of the present application, the organic hole functional material is an organic hole injection material, and the film layer obtained after drying the second film layer is a hole injection layer. After the step of drying the second film layer and before the step of obtaining the hole functional layer, the method for preparing the light-emitting device also includes the step of: forming a hole transport layer on the side of the hole injection layer away from the bottom electrode.

[0111] In order to further improve the comprehensive performance of the light-emitting device, in some embodiments of the present application, the method for preparing the light-emitting device further includes the step of: forming an electronic functional layer between the cathode and the light-emitting layer. The structural composition of the electronic functional layer is described above. That is, when the light-emitting device is a positive structure, the bottom electrode is an anode and the top electrode is a cathode. Before step S2, the method for preparing the light-emitting device further includes the steps of: forming an electronic functional layer on the side of the light-emitting layer away from the bottom electrode; the top electrode is formed on the side of the electronic functional layer away from the light-emitting layer. When the light-emitting device is an inverted structure, the bottom electrode is a cathode and the top electrode is an anode. Before the step of forming the light-emitting layer on one side of the bottom electrode, the method for preparing the light-emitting device further includes the steps of: forming an electronic functional layer on one side of the bottom electrode; the light-emitting layer is formed on the side of the electronic functional layer away from the bottom electrode.

[0112] It should be noted that, in addition to the hole functional layer, the preparation methods of other functional film layers in the light-emitting device include but are not limited to chemical methods and / or physical methods. Among them, the chemical method includes but is not limited to one or more of chemical vapor deposition, continuous ion layer adsorption and reaction, anodization, electrolytic deposition and co-precipitation. Physical methods include but are not limited to physical plating and solution methods. Physical plating methods include but are not limited to thermal evaporation, electron beam evaporation, magnetron sputtering, multi-arc ion plating, physical vapor deposition, atomic layer deposition and pulsed laser deposition. One or more of the solution method includes but is not limited to spin coating, printing, inkjet printing, scraping, printing, dip-pull, immersion, spraying, roll coating, casting, slit coating and strip coating. When a solution method is used to form a functional film layer, a drying process needs to be added to transform the wet film into a cured film. The drying process includes but is not limited to heat treatment, vacuum drying, air drying, etc. Among them, for the functional film layer located above the light-emitting layer (the material is an inorganic compound, especially inorganic nanoparticles), after a cured film is formed by a low-temperature (temperature not higher than 80°C) drying process such as vacuum drying and air drying, in order to further improve the film quality, the cured film can be further annealed by a process that can control the annealing depth, such as pulsed laser annealing, electron beam annealing, atomic annealing, infrared radiation annealing, etc.

[0113] After the preparation of each functional film layer of the light-emitting device is completed, a packaging process is required. The packaging process can be carried out by common machine packaging or manual packaging. In the packaging process environment, the oxygen content and water content are both lower than 0.1ppm to ensure the stability of the light-emitting device.

[0114] The embodiment of the present application also provides an electronic device, the electronic device includes any one of the light-emitting devices described in the embodiments of the present application, or the electronic device includes a light-emitting device prepared by any one of the preparation methods described in the embodiments of the present application. The electronic device can be any electronic product with a display function, including but not limited to a smart phone, a tablet computer, a laptop computer, a digital camera, a digital video camera, a smart wearable device, a smart weighing electronic scale, a car display, a television or an e-book reader, wherein the smart wearable device can be, for example, a smart bracelet, a smart watch, a virtual reality (VR) helmet, etc.

[0115] The technical scheme and technical effects of the present application are described in detail below through specific embodiments, comparative examples and experimental examples. The following embodiments are only some embodiments of the present application and do not specifically limit the present application.

[0116] Example 1

[0117] This embodiment provides a light emitting device and a method for preparing the same. The light emitting device is a quantum dot light emitting diode of a positive structure, such as Figure 4 As shown, in the direction from bottom to top, the light-emitting device 1 includes a substrate 10, an anode 11, a hole functional layer 14, a light-emitting layer 13, an electronic functional layer 15 and a cathode 12 arranged in sequence, wherein the hole functional layer 14 is composed of a hole injection layer 141 and a hole transport layer 142 stacked together, the hole injection layer 141 is closer to the anode 11 than the hole transport layer 142, and the electronic functional layer 15 is a single-layer structure.

[0118] The materials and thicknesses of the various layers in the light emitting device 1 are:

[0119] The material of the substrate 10 is glass, and the thickness of the substrate 10 is 2 mm;

[0120] The material of the anode 11 is ITO, and the thickness of the anode 11 is 50 nm;

[0121] The material of the cathode 12 is Ag, and the thickness of the cathode 12 is 100 nm;

[0122] The material of the light-emitting layer 13 is CdSe blue quantum dots, the average particle size of the quantum dots is 7nm, and the thickness of the light-emitting layer 13 is 40nm;

[0123] The material of the hole injection layer 141 is composed of PEDOT:PSS and a magnetic material. The mass ratio of the total mass of the magnetic material in the hole injection layer 141 to the mass ratio of PEDOT:PSS is 1:20. The magnetic material is composed of a first magnetic nanoparticle, a second magnetic nanoparticle and a third magnetic nanoparticle. The first magnetic nanoparticle to the third magnetic nanoparticle are all Fe3O4 modified with polylysine carrying a positive charge. The average particle size of the first magnetic nanoparticle is 2nm, the average particle size of the second magnetic nanoparticle is 5nm, and the average particle size of the third magnetic nanoparticle is 8nm. The mass ratio of the first magnetic nanoparticle: the second magnetic nanoparticle: the third magnetic nanoparticle is 3:1:1. In the hole injection layer 141, the first magnetic nanoparticle to the third magnetic nanoparticle are distributed in an orderly gradient. In the direction from the anode 11 to the light-emitting layer 13, the third magnetic nanoparticle to the first magnetic nanoparticle are arranged in sequence, that is, the first magnetic nanoparticle is closer to the light-emitting layer 13 than the third magnetic nanoparticle. The thickness of the hole injection layer 141 is 40nm.

[0124] The material of the hole transport layer 142 is poly[(9,9-dioctylfluorenyl-2,7-diyl)-co-(4,4'-(N-(p-butylphenyl))diphenylamine)] (abbreviated as TFB, CAS No. 223569-31-1), and the thickness of the hole transport layer 142 is 20 nm;

[0125] The material of the electronic functional layer 15 is nano ZnO (with an average particle size of 4 nm), and the thickness of the electronic functional layer 15 is 40 nm.

[0126] The method for preparing the light emitting device in this embodiment includes the following steps:

[0127] S1.1, providing a substrate, vapor-depositing ITO on one side of the substrate to obtain an ITO layer, then sequentially ultrasonically cleaning the substrate containing ITO with acetone for 15 minutes, ultrasonically cleaning with a detergent for 15 minutes, ultrasonically cleaning with deionized water for 15 minutes, and ultrasonically cleaning with isopropanol for 15 minutes, and after drying, performing a UV-ozone surface treatment for 20 minutes to obtain a substrate containing an anode;

[0128] S1.2. Take 60 mg of the first magnetic nanoparticles, 20 mg of the second magnetic nanoparticles and 20 mg of the third magnetic nanoparticles and evenly disperse them in 10 mL of toluene to obtain a magnetic material solution with a concentration of 10 mg / mL, mix 0.1 mL of the magnetic material solution with 4 mL of a PEDOT:PSS aqueous solution (PEDOT:PSS concentration is 5 mg / mL) to obtain a hole injection material solution, and then spin-coat the hole injection material solution on the side of the anode away from the substrate at room temperature and pressure in a nitrogen environment with a second magnetic field (constant magnetic field), and the spin coating speed is 4000 r / min. min, the spin coating time is 30s, that is, the action time of the second magnetic field is 30s, the direction of the second magnetic field is parallel to the side of the anode away from the substrate, the initial speed direction of the first magnetic nanoparticle to the third magnetic nanoparticle entering the second magnetic field is perpendicular to the magnetic field direction of the second magnetic field, the magnetic field forces received by the first magnetic nanoparticle to the third magnetic nanoparticle in the second magnetic field are the same, the second magnetic field is uniform in the region where the first magnetic nanoparticle to the third magnetic nanoparticle are located and the magnetic induction intensity is 0.5T, and a first film layer is obtained, and the first magnetic nanoparticle to the third magnetic nanoparticle are deposited on the side of the first film layer close to the anode;

[0129] S1.3. Remove the second magnetic field, and place the first film layer in the first magnetic field, so that the first magnetic nanoparticles to the third magnetic nanoparticles move in the direction away from the bottom electrode, and the direction of the movement speed of the first magnetic nanoparticles to the Nth magnetic nanoparticles is perpendicular to the magnetic field direction of the first magnetic field, until the third magnetic nanoparticles to the first magnetic nanoparticles are arranged in sequence along the vertical direction away from the bottom electrode to obtain the second film layer, wherein the direction of the first magnetic field is parallel to the side of the first film layer away from the anode, the magnetic field direction of the first magnetic field is opposite to the magnetic field direction of the second magnetic field, the magnetic field forces received by the first magnetic nanoparticles to the Nth magnetic nanoparticles in the first magnetic field are the same, the first magnetic field is uniform in the region where the first magnetic nanoparticles to the Nth magnetic nanoparticles are located, and the magnetic induction intensity is 0.5 T, and the processing time of the first magnetic field is 5s;

[0130] S1.4, removing the first magnetic field, placing the first film layer at a constant temperature of 150° C. for heat treatment to solidify the film, and obtaining a hole injection layer;

[0131] S1.5. In a nitrogen environment at room temperature and pressure, a TFB-chlorobenzene solution with a concentration of 8 mg / mL is spin-coated on the side of the hole injection layer away from the anode, and then subjected to a constant temperature heat treatment at 150° C. to solidify the film to obtain a hole transport layer;

[0132] S1.6. In a nitrogen environment at room temperature and pressure, a CdSe blue quantum dot-n-octane solution with a concentration of 20 mg / mL is spin-coated on the side of the hole transport layer away from the hole injection layer, and then subjected to a constant temperature heat treatment at 80°C to solidify the film to obtain a light-emitting layer;

[0133] S1.7, in a nitrogen environment at room temperature and pressure, spin-coat a 30 mg / mL nano ZnO-ethanol solution on the side of the light-emitting layer away from the hole transport layer, and then place it at 80°C for constant temperature heat treatment to solidify the film to obtain an electronic functional layer;

[0134] S1.8, place the laminated structure after step S1.6 in a vacuum no higher than 3×10 -4 In the evaporation chamber of Pa, Ag is thermally evaporated on the side of the electronic functional layer away from the light-emitting layer through a mask plate to obtain a cathode, which is then packaged to obtain a light-emitting device.

[0135] Among them, Fe3O4 magnetic nanoparticles can be purchased and customized. The preparation method of Fe3O4 magnetic nanoparticles, for example, includes the steps of preparing 200mL of 0.025mol / L FeCl2·6H2O solution, adding 120mL of 0.1mol / L potassium hydroxide under stirring to form Fe(OH)2 colloid, and simultaneously dropping 5wt% H2O2 aqueous solution (dropping different amounts can obtain Fe3O4 magnetic nanoparticles of different particle sizes), then solid-liquid separation and collecting precipitates, and then passing the obtained precipitates through a magnetic field (magnetic field strength of 0.35T) for magnetic separation, washing the separated Fe3O4 magnetic nanoparticles with distilled water and 95% alcohol in turn, and dispersing them in 95% alcohol to obtain a dispersion, and then performing surface poly-lysine modification treatment on the Fe3O4 magnetic nanoparticles in the dispersion so that the surfaces of the Fe3O4 magnetic nanoparticles carry charges.

[0136] Example 2

[0137] This embodiment provides a light-emitting device and a method for preparing the same. Compared with the method for preparing the light-emitting device in Embodiment 1, the method for preparing the light-emitting device in this embodiment is different only in that "the processing time of the first magnetic field is 5s" in step S1.3 is replaced by "the processing time of the first magnetic field is 10s".

[0138] Example 3

[0139] This embodiment provides a light-emitting device and a method for preparing the same. Compared with the method for preparing the light-emitting device in Embodiment 1, the method for preparing the light-emitting device in this embodiment is different only in that "the processing time of the first magnetic field is 5s" in step S1.3 is replaced by "the processing time of the first magnetic field is 15s".

[0140] Example 4

[0141] This embodiment provides a light-emitting device and a method for preparing the same. Compared with the light-emitting device in Embodiment 1, the light-emitting device in this embodiment is different only in that the mass ratio of the total mass of the magnetic material in the hole injection layer to PEDOT:PSS is replaced by "1:20" instead of "1:10".

[0142] Compared with the preparation method of the light-emitting device in Example 1, the difference in the preparation method of the light-emitting device in this embodiment is that: the "mixing 0.1 mL of the magnetic material solution with 4 mL of the PEDOT:PSS aqueous solution (PEDOT:PSS concentration is 5 mg / mL)" in step S1.2 is replaced by "mixing 0.2 mL of the magnetic material solution with 4 mL of the PEDOT:PSS aqueous solution (PEDOT:PSS concentration is 5 mg / mL)".

[0143] Example 5

[0144] This embodiment provides a light-emitting device and a method for preparing the same. Compared with the light-emitting device in Embodiment 1, the light-emitting device in this embodiment is different only in that the mass ratio of the total mass of the magnetic material in the hole injection layer to PEDOT:PSS is replaced by "1:20" instead of "1:5".

[0145] Compared with the preparation method of the light-emitting device in Example 1, the difference in the preparation method of the light-emitting device in this embodiment is that: the "mixing 0.1 mL of the magnetic material solution with 4 mL of the PEDOT:PSS aqueous solution (PEDOT:PSS concentration is 5 mg / mL)" in step S1.2 is replaced by "mixing 0.4 mL of the magnetic material solution with 4 mL of the PEDOT:PSS aqueous solution (PEDOT:PSS concentration is 5 mg / mL)".

[0146] Example 6

[0147] The present embodiment provides a light-emitting device and a preparation method thereof. Compared with the light-emitting device in Embodiment 1, the light-emitting device in the present embodiment is different only in that the "mass ratio of the first magnetic nanoparticles: the second magnetic nanoparticles: the third magnetic nanoparticles is 3:1:1" in the hole injection layer is replaced by "the mass ratio of the first magnetic nanoparticles: the second magnetic nanoparticles: the third magnetic nanoparticles is 5:3:2".

[0148] Compared with the preparation method of the light-emitting device in Example 1, the difference of the preparation method of the light-emitting device in this embodiment is that the step S1.2 of "take 60 mg of the first magnetic nanoparticles, 20 mg of the second magnetic nanoparticles and 20 mg of the third magnetic nanoparticles and evenly disperse them in 10 mL of toluene to obtain a magnetic material solution with a concentration of 10 mg / mL" is replaced by "take 50 mg of the first magnetic nanoparticles, 30 mg of the second magnetic nanoparticles and 20 mg of the third magnetic nanoparticles and evenly disperse them in 10 mL of toluene to obtain a magnetic material solution with a concentration of 10 mg / mL".

[0149] Example 7

[0150] The present embodiment provides a light-emitting device and a preparation method thereof. Compared with the light-emitting device in Embodiment 1, the light-emitting device in the present embodiment is different only in that the "mass ratio of the first magnetic nanoparticles: the second magnetic nanoparticles: the third magnetic nanoparticles is 3:1:1" in the hole injection layer is replaced by "the mass ratio of the first magnetic nanoparticles: the second magnetic nanoparticles: the third magnetic nanoparticles is 2:2:1".

[0151] Compared with the preparation method of the light-emitting device in Example 1, the difference of the preparation method of the light-emitting device in this embodiment is that: the step S1.2 "take 60 mg of the first magnetic nanoparticles, 20 mg of the second magnetic nanoparticles and 20 mg of the third magnetic nanoparticles and evenly disperse them in 10 mL of toluene to obtain a magnetic material solution with a concentration of 10 mg / mL" is replaced by "take 40 mg of the first magnetic nanoparticles, 40 mg of the second magnetic nanoparticles and 20 mg of the third magnetic nanoparticles and evenly disperse them in 10 mL of toluene to obtain a magnetic material solution with a concentration of 10 mg / mL".

[0152] Example 8

[0153] The present embodiment provides a light-emitting device and a preparation method thereof. Compared with the light-emitting device in Embodiment 1, the light-emitting device in the present embodiment is different only in that the "mass ratio of the first magnetic nanoparticles: the second magnetic nanoparticles: the third magnetic nanoparticles is 3:1:1" in the hole injection layer is replaced by "the mass ratio of the first magnetic nanoparticles: the second magnetic nanoparticles: the third magnetic nanoparticles is 4:3:3".

[0154] Compared with the preparation method of the light-emitting device in Example 1, the difference of the preparation method of the light-emitting device in this embodiment is that the step S1.2 of "take 60 mg of the first magnetic nanoparticles, 20 mg of the second magnetic nanoparticles and 20 mg of the third magnetic nanoparticles and uniformly disperse them in 10 mL of toluene to obtain a magnetic material solution with a concentration of 10 mg / mL" is replaced by "take 40 mg of the first magnetic nanoparticles, 30 mg of the second magnetic nanoparticles and 30 mg of the third magnetic nanoparticles and uniformly disperse them in 10 mL of toluene to obtain a magnetic material solution with a concentration of 10 mg / mL".

[0155] Example 9

[0156] The present embodiment provides a light-emitting device and a preparation method thereof. Compared with the light-emitting device in Embodiment 1, the light-emitting device in the present embodiment is different only in that the "mass ratio of the first magnetic nanoparticles: the second magnetic nanoparticles: the third magnetic nanoparticles is 3:1:1" in the hole injection layer is replaced by "the mass ratio of the first magnetic nanoparticles: the second magnetic nanoparticles: the third magnetic nanoparticles is 1:1:1".

[0157] Compared with the preparation method of the light-emitting device in Example 1, the difference of the preparation method of the light-emitting device in this embodiment is that: the step S1.2 "take 60 mg of the first magnetic nanoparticles, 20 mg of the second magnetic nanoparticles and 20 mg of the third magnetic nanoparticles and evenly disperse them in 10 mL of toluene to obtain a magnetic material solution with a concentration of 10 mg / mL" is replaced by "take 33.3 mg of the first magnetic nanoparticles, 33.3 mg of the second magnetic nanoparticles and 33.3 mg of the third magnetic nanoparticles and evenly disperse them in 10 mL of toluene to obtain a magnetic material solution with a concentration of 10 mg / mL".

[0158] Example 10

[0159] Compared with the light-emitting device in Example 1, the light-emitting device in this embodiment is different only in that the "PEDOT:PSS" in the hole injection layer is replaced by "2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene (HATCN)". The preparation method of the light-emitting device in this embodiment is carried out with reference to Example 1.

[0160] Embodiment 11

[0161] This embodiment provides a light-emitting device and a method for preparing the same. Compared with the light-emitting device in Embodiment 1, the light-emitting device in this embodiment is different only in that the hole transport layer is omitted.

[0162] Compared with the preparation method of the light-emitting device in Example 1, the difference of the preparation method of the light-emitting device in this embodiment is that: step S1.4 is omitted, and step S1.5 is replaced by "under a nitrogen environment at room temperature and pressure, spin-coat a CdSe blue quantum dot-n-octane solution with a concentration of 20 mg / mL on the side of the hole injection layer away from the anode, and then place it at 80°C for constant temperature heat treatment to solidify into a film to obtain a light-emitting layer."

[0163] Example 12

[0164] The present embodiment provides a light-emitting device and a preparation method thereof. Compared with the light-emitting device in Example 1, the light-emitting device in the present embodiment is different only in that the material of the hole injection layer is different. In the present embodiment, the hole injection layer is composed of PEDOT:PSS and a magnetic material. The mass ratio of the total mass of the magnetic material in the hole injection layer 141 to PEDOT:PSS is 1:20. The magnetic material is composed of first magnetic nanoparticles (the same as the first magnetic nanoparticles in Example 1) and second magnetic nanoparticles (the same as the second magnetic nanoparticles in Example 1). The mass ratio of the first magnetic nanoparticles to the second magnetic nanoparticles is 1:1. In the direction from the anode to the light-emitting layer, the second magnetic nanoparticles to the first magnetic nanoparticles are arranged in sequence, that is, the first magnetic nanoparticles are closer to the light-emitting layer than the second magnetic nanoparticles. The thickness of the hole injection layer is 40nm.

[0165] Compared with the preparation method of the light-emitting device in Example 1, the difference in the preparation method of the light-emitting device in this comparative example is that the method of preparing the light-emitting device in step S1.2 "take 60 mg of the first magnetic nanoparticles, 20 mg of the second magnetic nanoparticles and 20 mg of the third magnetic nanoparticles and uniformly disperse them in 10 mL of toluene to obtain a magnetic material solution with a concentration of 10 mg / mL" is replaced by "take 50 mg of the first magnetic nanoparticles and 50 mg of the second magnetic nanoparticles and uniformly disperse them in 10 mL of toluene to obtain a magnetic material solution with a concentration of 10 mg / mL".

[0166] Comparative Example 1

[0167] This comparative example provides a light-emitting device and a preparation method thereof. Compared with the light-emitting device in Example 1, the light-emitting device in this comparative example is different only in that the material of the hole injection layer is replaced by PEDOT:PSS.

[0168] Compared with the preparation method of the light-emitting device in Example 1, the difference of the preparation method of the light-emitting device in this comparative example is only that: step S1.2 is replaced by "under a nitrogen environment at room temperature and pressure, spin-coat a PEDOT:PSS aqueous solution with a concentration of 5 mg / mL on the side of the anode away from the substrate, and then place it at a constant temperature heat treatment of 150°C to solidify into a film to obtain a hole injection layer", and steps S1.3 and S1.4 are omitted.

[0169] Comparative Example 2

[0170] This comparative example provides a light-emitting device and a preparation method thereof. Compared with the light-emitting device in Example 1, the light-emitting device in this comparative example is different only in that the material of the hole injection layer is replaced by HATCN.

[0171] Compared with the preparation method of the light-emitting device in Example 1, the difference of the preparation method of the light-emitting device in this comparative example is only that: step S1.2 is replaced by "under a nitrogen environment at room temperature and pressure, spin-coat a HATCN-ethyl benzoate solution with a concentration of 5 mg / mL on the side of the anode away from the substrate, and then place it at a constant temperature heat treatment of 150°C to solidify into a film to obtain a hole injection layer", and step S1.3 and step S1.4 are omitted.

[0172] Comparative Example 3

[0173] This comparative example provides a light-emitting device and a preparation method thereof. Compared with the light-emitting device in Example 1, the light-emitting device in this comparative example is different only in that the first to third magnetic nanoparticles are mixedly distributed in the hole injection layer.

[0174] Compared with the preparation method of the light-emitting device in Example 1, the only difference in the preparation method of the light-emitting device in this comparative example is that: step S1.2 is replaced by "take 60 mg of the first magnetic nanoparticles, 20 mg of the second magnetic nanoparticles and 20 mg of the third magnetic nanoparticles and evenly disperse them in 10 mL of toluene to obtain a magnetic material solution with a concentration of 10 mg / mL, mix 0.1 mL of the magnetic material solution with 4 mL of PEDOT:PSS aqueous solution (PEDOT:PSS concentration is 5 mg / mL) to obtain a hole injection material solution, and then under a nitrogen environment at room temperature and pressure, spin coat the hole injection material solution on the side of the anode away from the substrate, and then place it at 150°C for constant temperature heat treatment to solidify into a film to obtain a hole injection layer".

[0175] Comparative Example 4

[0176] This comparative example provides a light-emitting device and a preparation method thereof. Compared with the light-emitting device in Example 1, the light-emitting device in this comparative example is different only in that PEDOT:PSS in the hole injection layer is replaced by HATCN, and the first to third magnetic nanoparticles are mixed and distributed in the hole injection layer.

[0177] Compared with the preparation method of the light-emitting device in Example 1, the only difference in the preparation method of the light-emitting device in this comparative example is that: step S1.2 is replaced by "take 60 mg of the first magnetic nanoparticles, 20 mg of the second magnetic nanoparticles and 20 mg of the third magnetic nanoparticles and evenly disperse them in 10 mL of toluene to obtain a magnetic material solution with a concentration of 10 mg / mL, mix 0.1 mL of the magnetic material solution with 4 mL of HATCN-ethyl benzoic acid solution with a concentration of 5 mg / mL to obtain a hole injection material solution, and then under a nitrogen environment at room temperature and pressure, spin coat the hole injection material solution on the side of the anode away from the substrate, and then place it at 150°C for constant temperature heat treatment to solidify into a film to obtain a hole injection layer".

[0178] Comparative Example 5

[0179] This comparative example provides a light-emitting device and a preparation method thereof. Compared with the light-emitting device in Example 1, the light-emitting device in this comparative example is different only in that the material of the hole injection layer is replaced with PEDOT:PSS, and the hole transport layer is omitted.

[0180] Compared with the preparation method of the light-emitting device in Example 1, the difference of the preparation method of the light-emitting device in this comparative example is that: step S1.2 is replaced by "under a nitrogen environment at room temperature and pressure, spin-coat a PEDOT:PSS aqueous solution with a concentration of 5 mg / mL on the side of the anode away from the substrate, and then place it at 150°C for constant temperature heat treatment to solidify into a film to obtain a hole injection layer", and step S1.3 and step S1.4 are omitted, and step S1.5 is replaced by "under a nitrogen environment at room temperature and pressure, spin-coat a CdSe blue quantum dot-n-octane solution with a concentration of 20 mg / mL on the side of the hole injection layer away from the anode, and then place it at 80°C for constant temperature heat treatment to solidify into a film to obtain a light-emitting layer".

[0181] Comparative Example 6

[0182] This comparative example provides a light-emitting device and a preparation method thereof. Compared with the light-emitting device in Example 1, the light-emitting device in this comparative example is different only in that the material of the hole injection layer is replaced with HATCN, and the hole transport layer is omitted.

[0183] Compared with the preparation method of the light-emitting device in Example 1, the difference of the preparation method of the light-emitting device in this comparative example is that: step S1.2 is replaced by "under a nitrogen environment at room temperature and pressure, spin-coat a HATCN-ethyl benzoic acid solution mixture with a concentration of 5 mg / mL on the side of the anode away from the substrate, and then place it at 150°C for constant temperature heat treatment to solidify into a film to obtain a hole injection layer", and step S1.3 and step S1.4 are omitted, and step S1.5 is replaced by "under a nitrogen environment at room temperature and pressure, spin-coat a CdSe blue quantum dot-n-octane solution with a concentration of 20 mg / mL on the side of the hole injection layer away from the anode, and then place it at 80°C for constant temperature heat treatment to solidify into a film to obtain a light-emitting layer".

[0184] Experimental Example 1

[0185] In the preparation process of the light-emitting devices in Examples 1 to 12 and Comparative Examples 1 to 4, after the hole injection layer is prepared, an atomic force microscope (AFM) is used to observe the surface morphology of the hole injection layer of the light-emitting devices in Examples 1 to 12 and Comparative Examples 1 to 4. The surface roughness Ra (profile arithmetic mean) of the hole injection layer of the light-emitting devices in Examples 1 to 12 and Comparative Examples 1 to 4 is detected, and the detection results are shown in Table 1 below:

[0186] Table 1 List of surface roughness Ra of hole injection layer

[0187]

[0188]

[0189] As can be seen from Table 1, compared with the Ra of the hole injection layer of the light-emitting device in Comparative Examples 3 to 4, the Ra of the hole injection layer of the light-emitting device in Examples 1 to 12 is significantly reduced. In addition, compared with the Ra of the hole injection layer of the light-emitting device in Comparative Examples 1 and 2, the Ra of the hole injection layer of the light-emitting device in Examples 1 to 11 is less different, which shows that: compared with the first magnetic nanoparticles to the third magnetic nanoparticles mixedly distributed in the hole injection layer, the first magnetic nanoparticles to the third magnetic nanoparticles are distributed in the hole injection layer in a gradient, which can improve the surface flatness of the hole injection layer, and its film quality is close to that of the hole injection layer made of organic hole injection materials.

[0190] Experimental Example 2

[0191] A first single-hole device to an eighteenth single-hole device are provided. In a direction from bottom to top, each single-hole device is composed of a substrate, an anode, a hole functional layer, a light-emitting layer and a cathode which are stacked in sequence, and the structural composition of the substrate, anode, light-emitting layer and cathode in each single-hole device is respectively the same as the structural composition of the corresponding functional layer of the light-emitting device in Example 1. For example, the light-emitting layer in each single-hole device is the same as the structural composition of the light-emitting layer of the light-emitting device in Example 1.

[0192] The structural composition of the hole functional layer in the first single-hole device to the eighteenth single-hole device is respectively the same as the structural composition of the light-emitting layer in Examples 1 to 12 and Comparative Examples 1 to 6. For example, the structural composition of the hole functional layer in the first single-hole device is the same as the structural composition of the hole functional layer in Example 1, and the structural composition of the hole functional layer in the eighteenth single-hole device is the same as the structural composition of the hole functional layer in Comparative Example 6.

[0193] The performance of the first to eighteenth single-hole devices was tested, and the voltage (U) of each single-hole device under the drive of a constant current (2 mA) was obtained by using the optical property measurement equipment of FPD (including Ocean Optics USB2000, LabView-controlled QE-PRO spectrometer, Keithley 2400, high-precision digital source meter Keithley 6485, an optical fiber with an inner diameter of 50 μm, device test probes and fixtures, various related connecting wires and data cards, an efficiency test cassette and a data acquisition system). HOD ,V). The test environment conditions are: ambient temperature 25℃, ambient humidity 50%.

[0194] The performance test data of each single hole device is as shown in Table 2 below:

[0195] Table 2 Performance test data of the first single hole device to the eighteenth single hole device

[0196]

[0197]

[0198] It can be seen from Table 2 that compared with the thirteenth to eighteenth single-hole devices, the U HOD The hole injection level of the first single hole device to the twelfth single hole device is lower, that is, the hole injection level of the first single hole device to the twelfth single hole device is higher. It can be seen that by adding the first magnetic nanoparticle to the third (second) magnetic nanoparticle in the hole functional layer, and the first magnetic nanoparticle to the third (second) magnetic nanoparticle presents a gradient and orderly distribution, the hole functional layer can have an energy level gradient, thereby reducing the barrier of hole injection into the light-emitting layer, and effectively improving the hole mobility.

[0199] For the fifteenth single-hole device and the sixteenth single-hole device, although the first to third magnetic nanoparticles are doped in the hole functional layer, the first to third magnetic nanoparticles are mixedly distributed and cannot effectively reduce the barrier for hole injection into the light-emitting layer, but also cause the surface roughness of the hole functional layer to increase. Therefore, the hole injection levels of the fifteenth single-hole device and the sixteenth single-hole device are lower than those of the first to eleventh single-hole devices.

[0200] For the seventeenth single-hole device and the eighteenth single-hole device, the hole transport layer is omitted, resulting in a decrease in the hole injection level. The hole injection level of the eleventh single-hole device is higher than that of the seventeenth single-hole device and the eighteenth single-hole device because: although the hole transport layer is omitted, the hole injection layer is doped with the first magnetic nanoparticle to the third magnetic nanoparticle, and the first magnetic nanoparticle to the third magnetic nanoparticle are distributed in a gradient order, which effectively reduces the barrier of hole injection into the light-emitting layer, thereby improving the hole injection level.

[0201] Experimental Example 3

[0202] The performance of the light-emitting devices packaged in Examples 1 to 12 and Comparative Examples 1 to 6 was tested, and the parameters such as the start-up voltage, current, maximum brightness, and luminous spectrum of each light-emitting device were obtained by using a FPD optical property measurement device, and the device life of each light-emitting device was tested using a life test device. The test environment conditions are: ambient temperature 25°C, ambient humidity 50%.

[0203] The external quantum efficiency test method is: use EQE optical test instrument to detect the external quantum efficiency of each light-emitting device, and calculate the maximum external quantum efficiency (EQE max ,%).

[0204] The device life detection method includes the following steps: under the drive of a constant current (2mA), using a life test equipment to perform electroluminescence life analysis on each light-emitting device, recording the time required for each light-emitting device to decay from the maximum brightness to 95%, and calculating the time required for the brightness of each single-hole device to decay from 100% to 95% at a brightness of 1000nit through a decay fitting formula (LT95@1knit,h).

[0205] The performance test data of each light emitting device is detailed in Table 3 below:

[0206] Table 3 Summary of performance test data of light emitting devices in Examples 1 to 12 and Comparative Examples 1 to 6

[0207]

[0208] It can be seen from Table 3 that, compared with the comprehensive performance of the light-emitting devices in Comparative Examples 1 to 6, the comprehensive performance of the light-emitting devices in Examples 1 to 12 is more advantageous, specifically, the light-emitting efficiency of the light-emitting devices in Examples 1 to 12 is higher, and the device life of the light-emitting devices in Examples 1 to 12 is longer. Taking the light-emitting devices in Example 1 and Comparative Example 1 as examples, the EQE of the light-emitting device in Example 5 is max is the EQE of the light-emitting device in Comparative Example 2 max The LT95@1knit of the light-emitting device in Example 5 is 1.9 times that of the light-emitting device in Comparative Example 2, and the LT95@1knit of the light-emitting device in Example 5 is 2.6 times that of the light-emitting device in Comparative Example 2.

[0209] It can be seen from this that by doping the first magnetic nanoparticles to the third magnetic nanoparticles into the hole functional layer, and the first magnetic nanoparticles to the third magnetic nanoparticles present a gradient and orderly distribution, the hole functional layer can have an energy level gradient, thereby reducing the barrier for hole injection into the light-emitting layer, effectively improving the hole mobility, and promoting the electron-hole transfer balance of the light-emitting device, thereby improving the luminous efficiency and device life of the light-emitting device.

[0210] For the light-emitting devices in Comparative Examples 3 and 4, although the hole functional layer is doped with the first to third magnetic nanoparticles, the first to third magnetic nanoparticles are mixedly distributed and cannot effectively reduce the barrier for hole injection into the light-emitting layer, but also cause the surface roughness of the hole functional layer to increase, thereby limiting the degree of improvement in the overall performance of the light-emitting device.

[0211] In addition, the hole transport layer is omitted in the light-emitting device in Comparative Examples 5 and 6, and the hole injection layer is not doped with magnetic nanoparticles, so that the overall performance of the light-emitting device is poor. In addition, although the hole transport layer is omitted in the light-emitting device in Example 11, the hole injection layer is doped with the first magnetic nanoparticle to the third magnetic nanoparticle, and the first magnetic nanoparticle to the third magnetic nanoparticle are distributed in an orderly gradient, which effectively reduces the potential barrier of hole injection into the light-emitting layer and improves the hole injection level, so that the overall performance of the light-emitting device is better than that of the light-emitting device in Comparative Examples 5 and 6.

[0212] The above is a detailed introduction to a light-emitting device, a method for preparing a light-emitting device, and an electronic device provided in the embodiments of the present application. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the technical solutions and core ideas of the present application; ordinary technicians in this field should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some of the technical features therein by equivalents; and these modifications or replacements do not make the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A light emitting device, characterized in that: include: An anode and a cathode arranged opposite to each other; A light-emitting layer is disposed between the anode and the cathode; as well as A hole functional layer is disposed between the anode and the light-emitting layer; Among them, the material of the hole functional layer includes organic hole functional material and magnetic material, the magnetic material includes first magnetic nanoparticles to N-th magnetic nanoparticles, the average particle size of the first magnetic nanoparticles to the average particle size of the N-th magnetic nanoparticles gradually increases, and N is a positive integer greater than or equal to 2; along the direction from the anode to the light-emitting layer, the first magnetic nanoparticles to the N-th magnetic nanoparticles in the hole functional layer are arranged in sequence.

2. The light emitting device according to claim 1, characterized in that: The first magnetic nanoparticle to the Nth magnetic nanoparticle respectively carry positive charges, and / or the first magnetic nanoparticle to the Nth magnetic nanoparticle are made of the same material, and / or the first magnetic nanoparticle to the Nth magnetic nanoparticle have the same charge number; and / or The first to Nth magnetic nanoparticles are independently selected from one or more of iron, iron alloy, iron oxide, cobalt, cobalt alloy, cobalt oxide, nickel, nickel alloy and nickel oxide.

3. The light emitting device according to claim 1, characterized in that: The particle size distribution range of the magnetic material is 1 nm to 10 nm; and / or The N is 2, and the magnetic material consists of first magnetic nanoparticles and second magnetic nanoparticles, the average particle size of the first magnetic nanoparticles is 1nm to 6nm, and the average particle size of the second magnetic nanoparticles is 4nm to 10nm; or, the N is 3, and the magnetic material consists of first magnetic nanoparticles, second magnetic nanoparticles and third magnetic nanoparticles, the average particle size of the first magnetic nanoparticles is 1nm to 3nm, the average particle size of the second magnetic nanoparticles is 4nm to 6nm, and the average particle size of the third magnetic nanoparticles is 6nm to 10nm.

4. The light emitting device according to claim 1, characterized in that: In the hole functional layer, the mass of the first magnetic nanoparticle to the Nth magnetic nanoparticle is the same as each other; or, the mass of the first magnetic nanoparticle to the Nth magnetic nanoparticle gradually decreases; and / or The organic hole functional material is an organic hole injection material, and the organic hole injection material is selected from poly (3,4-ethylenedioxythiophene): poly (styrene sulfonic acid), copper phthalocyanine, titanium phthalocyanine, 2,3,5,6-tetrafluoro-7,7',8,8'-tetracyanodimethyl-p-benzoquinone, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, poly (9-vinyl carbazole), poly [bis (4-phenyl) (4-butylphenyl) amine], N,N'-bis [4- [bis (3-methylphenyl) amino] phenyl] -N,N'-diphenyl-biphenyl-4,4'-diamine, 4,4',4"-tri (carbazole-9-yl) triphenylamine, poly [(9,9-dioctylfluorenyl-2,7- One or more of N,N'-diphenyl-N,N'-di(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine, N,N'-bis(1-naphthyl)-N,N'-diphenyl-1,1'-diphenyl-4,4'-diamine, 4,4'-cyclohexylbis[N,N-di(4-methylphenyl)aniline], 4,4',4'-tris(N-3-methylphenyl-N-phenylamino)triphenylamine, N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine, polythiophene, polyaniline and polytriphenylamine; and / or The material of the hole functional layer consists of the organic hole functional material and the magnetic material.

5. The light emitting device according to any one of claims 1 to 4, characterized in that: In the hole functional layer, the mass ratio of the magnetic material to the organic hole functional material is 1:(5-20).

6. The light emitting device according to claim 1, characterized in that: The material of the light-emitting layer comprises one or more of an organic light-emitting material and quantum dots, wherein the organic light-emitting material is selected from one or more of 4,4'-bis(N-carbazole)-1,1'-biphenyl:tri[2-(p-tolyl)pyridine iridium(III), 4,4',4"-tri(carbazole-9-yl)triphenylamine:tri[2-(p-tolyl)pyridine iridium, diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials, DBP fluorescent materials, delayed fluorescent materials, TTA materials, thermally activated delayed materials, polymers containing BN covalent bonds, hybrid localized charge transfer excited state materials and exciplex light-emitting materials; The quantum dots are selected from one or more of single-component quantum dots, core-shell quantum dots, inorganic perovskite quantum dots, organic perovskite quantum dots and organic-inorganic hybrid perovskite quantum dots; the material of the single-component quantum dots, the material of the core of the core-shell quantum dots and the material of the shell of the core-shell quantum dots are independently selected from at least one of II-VI compounds, III-V compounds, IV-VI compounds or I-III-VI compounds, wherein the II-VI compounds are selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdS One or more of CdS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, wherein the III-V group compound is selected from GaN, GaP, GaAs, GaS b, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, One or more of InAlPAs and InAlPSb, the IV-VI group compound is selected from one or more of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe and SnPbSTe, and the I-III-VI group compound is selected from one or more of CuInS, CuInSe and AgInS; the general structural formula of the inorganic perovskite quantum dot is AMX3, wherein A is Cs + ion, M is a divalent metal cation, M is selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ and Eu 2+ One or more of, X is a halogen anion; the general structural formula of the organic perovskite quantum dot is CMX3, C is a carboxamidine group; the general structural formula of the organic-inorganic hybrid perovskite quantum dot is BMX3, B is selected from an organic amine cation; and / or The light-emitting device further comprises an electronic functional layer disposed between the cathode and the light-emitting layer, wherein a material of the electronic functional layer comprises one or more of a first metal oxide, 8-hydroxyquinoline lithium, cesium carbonate, cesium fluoride, cesium azide, lithium fluoride, an organic phosphorus oxide, an organic thiophosphine compound, and an organic selenophosphine compound, wherein the first metal oxide is selected from one or more of zinc oxide, titanium oxide, tin oxide, barium oxide, tantalum oxide, aluminum oxide, zirconium oxide, magnesium zinc oxide, calcium zinc oxide, zirconium zinc oxide, gallium zinc oxide, aluminum zinc oxide, lithium zinc oxide, titanium zinc oxide, yttrium zinc oxide, indium tin oxide, and lithium titanium oxide; and / or The materials of the anode and the cathode are independently selected from one or more of metals, carbon materials and second metal oxides, the metals are selected from one or more of Al, Ag, Cu, Mo, Au, Ba, Pt, Ca, Ir, Ni and Mg, the carbon materials are selected from one or more of graphite, carbon nanotubes, graphene and carbon fibers, and the second metal oxides are selected from one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide, aluminum-doped magnesium oxide, SnO2, ZnO and In2O3.

7. A method for preparing a light emitting device, characterized in that: The steps include: providing a bottom electrode, and forming a light emitting layer on one side of the bottom electrode; and forming a top electrode on a side of the light emitting layer away from the bottom electrode; Wherein, when the light-emitting device is of a positive structure, the bottom electrode is an anode and the top electrode is a cathode, before the step of forming a light-emitting layer on one side of the bottom electrode, the method for preparing the light-emitting device further comprises the steps of: forming a hole functional layer on one side of the bottom electrode; the light-emitting layer is formed on a side of the hole functional layer away from the bottom electrode; Alternatively, when the light-emitting device is an inverted structure, the bottom electrode is a cathode and the top electrode is an anode, before the step of forming the top electrode on the side of the light-emitting layer away from the bottom electrode, the method for preparing the light-emitting device further comprises the steps of: forming a hole functional layer on the side of the light-emitting layer away from the bottom electrode; the top electrode is formed on the side of the hole functional layer away from the light-emitting layer; Among them, the material of the hole functional layer includes organic hole functional material and magnetic material, the magnetic material includes first magnetic nanoparticles to N-th magnetic nanoparticles, the average particle size of the first magnetic nanoparticles to the average particle size of the N-th magnetic nanoparticles gradually increases, and N is a positive integer greater than or equal to 2; along the direction from the anode to the light-emitting layer, the first magnetic nanoparticles to the N-th magnetic nanoparticles in the hole functional layer are arranged in sequence.

8. The preparation method according to claim 7, characterized in that: The first magnetic nanoparticle to the Nth magnetic nanoparticle respectively carry positive charges, and the method for forming the hole functional layer comprises the steps of: (A1) depositing a dispersion containing the organic hole functional material and the magnetic material to obtain a first film layer, wherein the first magnetic nanoparticles to the Nth magnetic nanoparticles are located on a side of the first film layer close to the bottom electrode; (A2) placing the first film layer in a first magnetic field so that the first magnetic nanoparticles to the Nth magnetic nanoparticles move in a direction away from the bottom electrode until the Nth magnetic nanoparticles to the first magnetic nanoparticles are arranged in sequence along a vertical direction away from the bottom electrode, thereby obtaining a second film layer; (A3) Drying the second film layer to obtain the hole functional layer.

9. The preparation method according to claim 8, characterized in that: The first magnetic field is a constant magnetic field; and / or The magnetic field forces exerted on the first magnetic nanoparticle to the Nth magnetic nanoparticle in the first magnetic field are the same, and / or the materials of the first magnetic nanoparticle to the Nth magnetic nanoparticle are the same, and / or the charges of the first magnetic nanoparticle to the Nth magnetic nanoparticle are the same; and / or In (A2), the magnetic field direction of the first magnetic field is parallel to a side of the first film layer away from the bottom electrode; and / or In the step of placing the first film layer in a first magnetic field so that the first magnetic nanoparticles to the Nth magnetic nanoparticles move in a direction away from the bottom electrode, the first magnetic nanoparticles to the Nth magnetic nanoparticles respectively have velocity components in a direction perpendicular to the magnetic field direction of the first magnetic field.

10. The preparation method according to claim 8 or 9, characterized in that: In (A1), the step of depositing a dispersion containing the organic hole functional material and the magnetic material is performed in an environment having a second magnetic field; or, after the step of depositing a dispersion containing the organic hole functional material and the magnetic material and before the step of obtaining the first film layer, the step further includes: placing the deposited dispersion in a second magnetic field; in the dispersion, the mass of the first magnetic nanoparticle to the mass of the Nth magnetic nanoparticle are the same; or, the mass of the first magnetic nanoparticle to the mass of the Nth magnetic nanoparticle gradually decreases; and / or The organic hole functional material is an organic hole injection material, and the organic hole injection material is selected from poly (3,4-ethylenedioxythiophene): poly (styrene sulfonic acid), copper phthalocyanine, titanium phthalocyanine, 2,3,5,6-tetrafluoro-7,7',8,8'-tetracyanodimethyl-p-benzoquinone, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, poly (9-vinyl carbazole), poly [bis (4-phenyl) (4-butylphenyl) amine], N,N'-bis [4- [bis (3-methylphenyl) amino] phenyl] -N,N'-diphenyl-biphenyl-4,4'-diamine, 4,4',4"-tri (carbazole-9-yl) triphenylamine, poly [(9,9-dioctylfluorenyl-2,7- One or more of N,N'-diphenyl-N,N'-di(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine, N,N'-bis(1-naphthyl)-N,N'-diphenyl-1,1'-diphenyl-4,4'-diamine, 4,4'-cyclohexylbis[N,N-di(4-methylphenyl)aniline], 4,4',4'-tris(N-3-methylphenyl-N-phenylamino)triphenylamine, N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine, polythiophene, polyaniline and polytriphenylamine; and / or In the dispersion, the mass ratio of the magnetic material to the organic hole functional material is 1:(5-20); and / or The first to Nth magnetic nanoparticles are independently selected from one or more of iron, iron alloy, iron oxide, cobalt, cobalt alloy, cobalt oxide, nickel, nickel alloy and nickel oxide; and / or The particle size distribution range of the magnetic material is 1 nm to 10 nm; and / or The N is 2, the magnetic material consists of a first magnetic nanoparticle and a second magnetic nanoparticle, the average particle size of the first magnetic nanoparticle is 1nm to 6nm, and the average particle size of the second magnetic nanoparticle is 4nm to 10nm; or, the N is 3, the magnetic material consists of a first magnetic nanoparticle, a second magnetic nanoparticle and a third magnetic nanoparticle, the average particle size of the first magnetic nanoparticle is 1nm to 3nm, the average particle size of the second magnetic nanoparticle is 4nm to 6nm, and the average particle size of the third magnetic nanoparticle is 6nm to 10nm; and / or The method for preparing the light-emitting device also includes the step of forming an electronic functional layer between the cathode and the light-emitting layer, wherein the material of the electronic functional layer comprises one or more of a first metal oxide, 8-hydroxyquinoline lithium, cesium carbonate, cesium fluoride, cesium azide, lithium fluoride, organic phosphorus oxide, organic thiophosphine compound and organic selenophosphine compound, wherein the first metal oxide is selected from one or more of zinc oxide, titanium oxide, tin oxide, barium oxide, tantalum oxide, aluminum oxide, zirconium oxide, magnesium zinc oxide, calcium zinc oxide, zirconium oxide, gallium zinc oxide, aluminum zinc oxide, lithium zinc oxide, titanium zinc oxide, yttrium zinc oxide, indium tin oxide and lithium titanium oxide.

11. The preparation method according to claim 10, characterized in that: The second magnetic field is a constant magnetic field, and / or the magnetic field forces exerted on the first magnetic nanoparticle to the Nth magnetic nanoparticle in the second magnetic field are the same; and / or The magnetic field direction of the second magnetic field is parallel to a surface of the bottom electrode close to the first film layer.

12. An electronic device, characterized in that: The electronic device comprises the light-emitting device as claimed in any one of claims 1 to 6, or a light-emitting device manufactured by the manufacturing method as claimed in any one of claims 7 to 11.